The role of secondary school principals in Sakaka city in dealing with crises: The Corona pandemic (COVID-19) as a model - Alsaleh, Rabab Turki; Alshamry, Gharbi Marji (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the role of secondary school principals in Sakaka during the Corona pandemic(COVID-19), and to identify the reality of the dealings of secondary school principals in Sakaka with the difficulties they faced during the Corona pandemic, and to identify the measures that can be taken by secondary school principals in Sakaka after the end of the Corona pandemic (COVID-19) from the female teachers’ point of view, and the detection of statistically significant differences in the reality of secondary school principals in Sakaka dealing with the difficulties they faced during the Corona pandemic (COVID-19) from the female teachers’ point of view according to the variables (specialization - educational qualification - number of years’ experience), and the descriptive analytical method was used, by preparing a questionnaire, and the study population was represented by all secondary school teachers in Sakaka city during the academic year 1441/1442 AH, and their number was (586) female teachers, and the study sample consisted of (234) female teachers, there was high approval Among the responses of the study sample members about (the difficulties faced by secondary school principals in Sakaka city during the Corona pandemic), where the general average was (3.95) and there was high agreement when using the study sample. The respondents of the study sample about (the reality of secondary school principals dealing with the difficulties they faced during the Corona pandemic), where the general average was (3.92) and there was high approval among the responses of the study sample members about (measures that can be taken by principals Secondary schools after the end of the Corona pandemic), where the general average was (4.07); in addition to the absence of statistically significant differences in the reality of secondary school principals in Sakaka city dealing with the difficulties they faced during the Corona pandemic (COVID-19) from the point of view of The parameters are attributed to the variable (specialization, academic qualification, number of years of experience), and in light of the results of the study, some recommendations and suggestions were formulated.